Could hepatitis B vaccine act as an adjuvant to lower risk and relapses of cancer?. (7th May 2019) - Altinoz, Meric A.; Ozpinar, Aysel; Ozpinar, Alp; Hacker, Emily; Elmaci, İlhan
Abstract: In this review article, we hypothesize that Hepatitis B Virus Vaccine (HBV‐V) and certain antigens of Hepatitis B Virus (HBV) could act as anticancer immunoadjuvants in addition to their role of preventing HBV‐associated liver cancer. Evidence suggests that in animal breast cancer and melanoma models, combining hepatitis B‐surface antigen (HBsAg) with other cancer antigens resulted in enhanced antitumour activity. HBsAg shares antigenic mimicry with healthy and malignant cells including squamous epithelia, thymic epithelia, bladder‐ and colon cancer cells. There exist anecdotal reports and small case series about spontaneous remission of leukaemias and neuroblastoma following acute HBV‐infection. Recent studies also exist showing HBV‐carrier state is a good prognostic factor for intrahepatic cholangiocarcinoma. Further epidemiological studies and animal experiments are necessary whether HBV‐Vs exert additional immunoadjuvant benefits besides lowering the risk of liver cancer.